Perkembangan Anak Usia 3–4 Tahun Berdasarkan Peran Orangtua Di Paud Juwita Harapan Sidoarjo - Azizah, Nurul; Rahmawati, Dita (Journal of Issues in Midwifery, 2017)
ABSTRACTThe role of parents is very important in the development of children. because at this time there is a rapid development of basic runs that influence and determine the development of children further research objectives to determine the development of children aged 3-4 years based on the role of parents.Analytic survey research design, with a total of 30 respondents. Variable research development of children aged 3-4 years and parents. Data collection used primary data through questionnaire and observation. The collected data is presented in the form of frequency distribution table, cross tabulation and analyzed descriptively without statistical test.The results showed the development of children aged 3-4 years in PAUD Juwita Harapan in accordance with the stage of development is more prevalent in mothers who play a positive role (100%)..Conclusion of research is all parents who have positive role to have children whose development according to the stages of development. While parents who play a negative role have children whose development is dubious. All parents should make efforts in meeting the basic needs of children (asah, asih, foster) for optimal child development process.